Broadband neurophysiological abnormalities in the medial prefrontal region of the default‐mode network in adults with ADHD. Issue 3 (18th November 2011) - Wilson, Tony W.; Franzen, John D.; Heinrichs‐Graham, Elizabeth; White, Matthew L.; Knott, Nichole L.; Wetzel, Martin W.
Abstract Previous investigations of the default‐mode network (DMN) in persons with attention‐deficit/hyperactivity disorder (ADHD) have shown reduced functional connectivity between the anterior and posterior aspects. This finding was originally demonstrated in adults with ADHD, then in youth with ADHD, and has been tentatively linked to ultra low frequency oscillations within the DMN. The current study evaluates the specificity of DMN abnormalities to neuronal oscillations in the ultra low frequency range, and examines the regional specificity of these DMN aberrations in medicated and unmedicated adults with, and those without ADHD. An individually matched sample of adults with and without ADHD completed 6‐minute sessions of resting‐state magnetoencephalography (MEG). Participants with ADHD were known responders to stimulant medications and completed two sessions (predrug/postdrug). MEG data were coregistered to the participant's MRI, corrected for head motion, fitted to a regional‐level source model, and subjected to spectral analyses to extract neuronal population activity in regions of the DMN. The unmedicated adults with ADHD exhibited broadband deficits in medial prefrontal cortices (MPFC), but not other DMN regions compared to adults without ADHD. Unmedicated patients also showed abnormal cross‐frequency coupling in the gamma range between the MPFC and posterior cingulate areas, and disturbed balance within the DMN as activity in posterior regions was stronger than frontal regions at beta and lower frequencies, which dissipated at higher γ‐frequencies. Administration of pharmacotherapy significantly increased prefrontal alpha activity (8–14 Hz) in adults with ADHD, and decreased the cross‐frequency gamma coupling. These results indicate that neurophysiological aberrations in the DMN of patients with ADHD are not limited to ultra slow oscillations, and that they may be primarily attributable to abnormal broadband activity in the MPFC. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.